E-COMMERCE AND INFORMATION SYSTEMS' SIGNIFICANCE IN HELPING ENTREPRENEURS MAKE DECISIONS - Wida Ningsih (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this study was to examine the effect of using e-commerce and information systems on entrepreneurial decisions. In addition, this study also examines differences in entrepreneurial decisions between students who have businesses and those who do not have previous entrepreneurship. The sampling method used was purposive sampling with predetermined criteria. This study used primary data by distributing questionnaires to 213 accounting students in Bandung. The results of testing the hypothesis show that the use of e-commerce and information systems influences entrepreneurial decisions. In addition, there are differences in entrepreneurial decisions between students who are entrepreneurs and those who are not.